2013
DOI: 10.1002/sia.5228
|View full text |Cite
|
Sign up to set email alerts
|

Ab‐Initio calculations of the CO adsorption and dissociation on substitutional Fe–Cu surface alloys relevant to Fischer–Tropsch Synthesis: bcc‐(Cu)Fe(100) and fcc‐(Fe)Cu(100)

Abstract: Direct CO dissociation is seen the main path of the first step in the Fischer-Tropsch Synthesis (FTS) on the reactive iron surfaces. Cu/Fe alloy film is addressed with various applications over face-centered-cubic (fcc)-Cu and body-centered-cubic (bcc)-Fe in the FTS, i.e. preventing iron carbide formation (through direct CO dissociation) by moderating the surface reactivity and facilitating the reduction of iron surfaces, respectively. In this study by density functional theory, the stable configurations of CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…57 These studies indicate an important dependence of reaction pathways on the surface composition and structure. Adding Cu into Fe modifies the surface electron distribution of the Fe catalyst, and the resulting change of catalyst composition and structure impacts the stability of reactants, intermediates, and transition states, 25,58,76,77 thus altering the dominant pathways.…”
Section: Resultsmentioning
confidence: 99%
“…57 These studies indicate an important dependence of reaction pathways on the surface composition and structure. Adding Cu into Fe modifies the surface electron distribution of the Fe catalyst, and the resulting change of catalyst composition and structure impacts the stability of reactants, intermediates, and transition states, 25,58,76,77 thus altering the dominant pathways.…”
Section: Resultsmentioning
confidence: 99%
“…The investigation of CO adsorption 19 and dissociation on the basis Fe/Cu surface alloy model 39,40 and Cu monolayer model on Fe surface 41 showed that Cu can re- Cu promotion were reported; and this might be partially due to the obscure of Cu existing way and the complex structures.…”
mentioning
confidence: 94%
“…There have been extensive theoretical studies on CO hydrogenation for higher alcohol synthesis (HAS) over Fe-based catalysts, with a focus on adding Cu to promote the product selectivity. Zhao et al investigated CO dissociation on Cu-doped Fe(100) surfaces and found that Cu doping reduces CO dissociation activity. An H-assisted dissociation path is more favorable than the direct dissociation path.…”
Section: Introductionmentioning
confidence: 99%